Mons Claudianus. Ostraca graeca et latina IV. The Quarry Texts: MONS CLAUDIANUS. Ostraca graeca et latina IV. The Quarry Texts. (O.Claud. 632-896.) Edited with Translation and Commentary by Adam Bülow-Jacobsen (Documents de fouilles 47) Institut français d’archéologie orientale. Le Caire, 2009. 367 sider inklusive indices, appendices og 74 sider plancher - Bülow-Jacobsen, Adam (AIGIS, 2024)
Intet.